Estrategias metodológicas para el fortalecimiento de la lectoescritura en el área de lengua y literatura en estudiantes de tercero de educación general básica de la unidad educativa 5 de Octubre del cantón Echeandía de la provincia de Bolívar en el año lectivo 2023 – 2024 - Acosta Ortiz, Anderson Alexander (2024)
In the research presented, the problem identified in the teacher of the third years of the “5 de Octubre” Educational Unit of Echandía has been addressed, where a lack of methodological strategies for strengthening reading and writing, lack of motivation, resources and time had been detected. . . Therefore, the objective was to establish the ideal methodological strategies for strengthening literacy in the area of Language and Literature in third-year students of Basic General Education of the Educational Unit “5 de Octubre” of the Echeandía Canton of the province of Bolívar in the 2023 - 2024 school year. Therefore, a qualitative approach was carried out with the purpose of identifying the methodologies that are feasible for strengthening literacy with bibliographic research and with an interview and classroom observation of the teacher that allowed collect detailed information. From the information collected, the necessary theoretical foundation was made to investigate the methodological strategies of literacy and allowed us to develop a proposal as a didactic manual of literacy where there will be different activities that will allow motivation and the development of critical thinking and creative.